Turnover and connectivity as drivers of mammalian persistence in highly fragmented landscapes - Beltrão, Mayara Guimarães; Jorge, Maria Luisa S.P.; Carmignotto, Ana Paula; Silveira, Luís Fábio; Galetti, Mauro [UNESP] (Elsevier, 2024)
Pernambuco Endemism Center (PEC) stands as the Brazilian Atlantic Forest region with the most pronounced history of deforestation and forest fragmentation, attributed to early European colonization and agricultural settlement. As a result, PEC is known as the global tropical forest experiencing both the highest fragmentation levels and extinction rates. The extent of biodiversity loss and the factors associated with biodiversity persistence at PEC remain a knowledge gap. To address this gap, we evaluated how forest cover, fragmentation and other landscape features are related to the mammal's persistence. Using baited camera traps, we sampled 21 landscapes dominated by hostile matrices in Alagoas. We examined the relationship between species composition, richness, abundance, and beta-diversity and seven predictors through Generalized Linear Models and Multiple Regressions on Distance Matrices. Our findings revealed the presence of 21 native mammals in the study area, representing nearly 78 % of the diversity expected for the PEC. Nevertheless, we also found a high proportion of species loss within each landscape (from 43 % to 76 %), and high levels of species turnover between landscapes. Considering landscapes metrics, mammals exhibited more pronounced responses to habitat fragmentation in contrast to habitat loss or other anthropogenic factors. We identified a positive relationship between connectivity and richness, while the number of patches negatively affected the abundance. Our results underscore the critical role of habitat connectivity in highly deforested and fragmented regions, where it becomes more important than forest cover. The pronounced species turnover is key in upholding regional diversity and is crucial to species persistence in the region.
Keywords: Beta-diversity; Defaunation; Landscape attributes; Pernambuco Endemism Center; Space use